Farmland Investments in Africa: Whats the Deal? - Luca Di Corato; Sebastian Hess (Fondazione Eni Enrico Mattei (FEEM), 2014)
Large-scale foreign investments in African farmland are rising and may contribute to agricultural productivity growth and economic development. However, host countries sometimes have to wait longer for the economic benefits to arrive than initially expected. In this respect, the timing of project development is crucial and depends on the economic incentives provided to the investors. We therefore present a dynamic stochastic programming model that reflects the typical bargaining situation concerning large land deals in Africa and allows the effect of market- and country-specific risks and taxation to be assessed. The model shows that commodity price volatility increases the value of the land development option, but slows down the land development process. Furthermore, it shows that host country attempts to negotiate fixed commitments to the speed of project development may run counter to the structure of economic incentives at the project site. The applicability of the model is demonstrated for a recent 10,000-hectare cotton project in Ethiopia. Response surface estimations suggest that Ethiopia has negotiated a contract under which it will receive about half the expected total project value, as long as it levies the regular corporate tax rate.
Keywords: C61; D81; F23; Q24; 330; Foreign Direct Investment; Land Leasing; Real Options; Nash Bargaining